2008
DOI: 10.1158/1055-9965.epi-07-2502
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Raw Cruciferous Vegetables is Inversely Associated with Bladder Cancer Risk

Abstract: Cruciferous vegetables contain isothiocyanates, which show potent chemopreventive activity against bladder cancer in both in vitro and in vivo studies. However, previous epidemiologic studies investigating cruciferous vegetable intake and bladder cancer risk have been inconsistent. Cooking can substantially reduce or destroy isothiocyanates, and could account for study inconsistencies. In this hospital-based case-control study involving 275 individuals with incident, primary bladder cancer and 825 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 31 publications
4
100
0
2
Order By: Relevance
“…More recent case-control studies found no overall effect of vegetable consumption on bladder cancer risk. [24][25][26][27] Two case-control studies found a protective effect of fruit consumption on bladder cancer risk. 24,25 Results from casecontrol studies are known to be sensitive to selection and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…More recent case-control studies found no overall effect of vegetable consumption on bladder cancer risk. [24][25][26][27] Two case-control studies found a protective effect of fruit consumption on bladder cancer risk. 24,25 Results from casecontrol studies are known to be sensitive to selection and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent modest reductions in the incidence of bladder cancer are attributed to decreasing exposure to tobacco smoking and to occupational carcinogens. Although diet might also influence bladder carcinogenesis, owing to the many potential carcinogens or chemopreventive nutrients therein, 11 no consistent association between intake of selected nutrients or micronutrients and bladder cancer has emerged. Other lifestyle habits have been widely investigated, such as intake of coffee, artificial sweeteners, hair dyes, and have not been materially associated with bladder cancer.…”
Section: Epidemiology Of Bladder Cancermentioning
confidence: 99%
“…Due to its anti-inflammatory and antibacterial properties, cabbage has widespread use in traditional medicine, in alleviation of symptoms associated with gastrointestinal disorders (gastritis, peptic and duodenal ulcers, irritable bowel syndrome) as well as in treatment of minor cuts and wounds and mastitis, improve the bioavailable content of nonheme iron (Chiplonkar et al, 1999). Cabbage is good detoxifier, which purifies blood and removes toxinsdue to the presence of vitamin C and sulphur (Tang et al, (2007) in good amount. The beneficial phytochemicals in cabbage help activate and stabilize the body's antioxidant and detoxification mechanisms that dismantle and eliminate cancer-producing substances (Brooks et al,, 2231-5209 (Online) All Rights Reserved © Applied and Natural Science Foundation www.jans.ansfoundation.org 2001).…”
Section: Introductionmentioning
confidence: 99%